Fabrication and characteristic of 3‐D porous thermoplastic polyurethane/deacetylated cellulose acetate composite foam with outstanding mechanical property and oil/water separation performance. Issue 22 (3rd March 2022) - Cui, Zhixiang; Fan, Yue; Liu, Xiaolong; Si, Junhui; Wang, Qianting
Abstract: Nowadays, the environmental problems caused by industrial oily wastewater and offshore oil leakage are becoming more and more serious. Here, the 3‐D porous polyurethane/deacetylated acetate cellulose (TPU/d‐CA) composite foam with outstanding mechanical property and oil/water separation performance was successfully prepared. The morphology, wettability, mechanical properties, and oil/water separation performances had been systematically studied. The results showed that TPU/d‐CA composite foam could be used as water and oil removing material, respectively, for a series of oil/water mixture only under gravity force, due to its lipophilicity and hydrophilicity. It has high‐separation flux, which can reach up to 43, 000 L/m 2 ·h and 85, 000 L/m 2 ·h for water and oil, respectively and all the separation efficiency exceeds 98%. It also can be used as adsorbent material to absorb various oils, and the absorption capacity for carbon tetrachloride reached up to 34 g/g. Moreover, it can selectively, rapidly, and continuously separate oil or water by assisted peristaltic pump. After 15 cycle times, its separation efficiency is still as high as 98%. It has excellent comprehensive mechanical properties and antifouling ability. These results indicated that 3‐D TPU/d‐CA composite foam has broadly application prospects in oil/water separation field. Abstract :